A global systematic review on conservation and domestication of Parkia biglobosa, an indigenous fruit tree species in Sub-Sahara African traditional parklands: current knowledge and future directions. - Houndonougbo, Sènanmi Hermann Juliano; Kassa, Barthelemy; Mensah, Sylvanus; SALAKO, Kolawolé Valère; Glèlè Kakaï, Romain Lucas; ASSOGBADJO, ACHILLE EPHREM (My University, 2020)
Parkia biglobosa (Jacq.) R. Br. ex G. Don is one of the most common traditional parkland tree species that generates vital non-timber forest products and benefits for local people in Sub-Saharan Africa. Despite its socio-economic importance and value for local and regional economies, the species has remained at infant stage of domestication, yet declining in the nature. While several studies addressed various ecological, social and economic aspects, systematic reviews and literature syntheses on current knowledge and research gaps are lacking, despite their relevance for future research directions. Based on research publications from ScienceDirect, Google Scholar and African Journals Online, we provide a systematic literature review of the current knowledge on the ecological, socio-economic, conservation, and domestication aspects of P. biglobosa. We also identified important research gaps and future prospects for the species conservation and domestication. From 2060 publications initially recorded, 221 received full-text assessment after screening, of which 184 scientific papers were finally reviewed. Approximately 75% of these studies were undertaken in three West-African countries: Nigeria, Burkina Faso and Benin. Critical analyses were presented in line with perspectives on ecological, socio-economic, conservation and domestication aspects. The review highlighted the critical research gaps in distributional ecology, tree physiology, plant demography, molecular biology, genomics and evolutionary biology, but also called for more research effort from Central and East Africa, where a limited number of publications was recorded on P. biglobosa, in spite of being within the native distribution range. Such investigations would help in decision-making and elaboration of breeding strategies, as steps towards sustainable use and domestication of the species in Africa.
Keywords: Agroforestry systems; Domestication; Indigenous fruit tree; Non-timber forest products; Africa